Knowledge, Awareness, and Perceived Barriers Regarding Cervical Cancer Screening Among Bangladeshi Women Suffering from Cervical Cancer: A Cross-sectional Study - Islam, Muhammed Mohibul; Sultana, Farhana; Rahman, Md Hasan Shahriar; Pia, Nandita Islam; Hasibuzzaman, Md. Al; Ahmed, Arman; Hasan, Mohammed Shamim; Mahmud, Md Kayes; Akter, Rabeya; Mostaq, Md. Saqline; Amin, Mohammad Nurul (UI Scholars Hub, 2023)
Background: This study aimed to evaluate the knowledge, awareness, and perceived barriers regarding cervical cancer screening among women in Bangladesh. Methods: A hospital-based survey was conducted from January to April 2021 among 200 female participants. Statistical analysis of this study was performed by using Stata 13 (StataCorp LP, 4905 Lakeway Drive, College Station, TX 77845, USA), where Chi-square test was used for the determination of the correlation among different variables. Results: Among the participants, 86.5% were rural residents, 96% were married, 87.5% were housewives, 47% were uneducated, and 93.5% lived on a husband’s income. Moreover, 84.5% hadn’t any family history of cancer, 91.5% had no knowledge about cervical self-examination, 74.5% and 61.5% never heard of screening programs and cervical cancer, respectively (p < 0.05). In addition, 23.5% knew that early sexual activity was a risk factor for cervical cancer. Again, the outcome of ideas about other people’s thinking (6%), the stigma of cancer diagnosis (15%), difficulty talking with doctors (5%), poor knowledge (12.5%), and fear of physicians and examiners (5%) were statistically significant (p < 0.05). Conclusions: This study revealed that most female respondents lack knowledge and awareness regarding cervical cancer. To improve this situation, appropriate and socially acceptable awareness programs are necessary.